2020
DOI: 10.1186/s40360-020-00435-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and time trends of hospitalized methadone exposures in the United States based on the Toxicology Investigators Consortium (ToxIC) case registry: 2010–2017

Abstract: Background: Methadone is well known for its long duration of action and propensity for mortality after an overdose. The present research was aimed at evaluating the clinical manifestations and time trends of methadone exposure in patients in US hospitals. Methods: We queried the American College of Medical Toxicology's Toxicology Investigators Consortium case registry for all cases of methadone exposure between January 1, 2010, and December 31, 2017. The collected information included demographic features, cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…20,25,27,32 The findings of the present study showed that poisoning by narcotics such as Opium (T40.0) and Methadone (T40.3) was common in men and some studies have been conducted in this regard that confirms this. 33,34 In Iran, morbidity, and mortality due to poisoning are more common in men due to easy access to medicine and drugs as well as their abuse. 4 A common cause of mortality in men was poisoning by narcotics, such as Opium (T40.0).…”
Section: Discussionmentioning
confidence: 99%
“…20,25,27,32 The findings of the present study showed that poisoning by narcotics such as Opium (T40.0) and Methadone (T40.3) was common in men and some studies have been conducted in this regard that confirms this. 33,34 In Iran, morbidity, and mortality due to poisoning are more common in men due to easy access to medicine and drugs as well as their abuse. 4 A common cause of mortality in men was poisoning by narcotics, such as Opium (T40.0).…”
Section: Discussionmentioning
confidence: 99%